2018
DOI: 10.1139/cjas-2016-0228
|View full text |Cite
|
Sign up to set email alerts
|

Castor bean cake detoxified with calcium hydroxide in diets for pigs at growing and finishing phases

Abstract: The present study was aimed to evaluate the use of increasing levels of castor bean cake detoxified with calcium hydroxide in diets for pigs at growing and finishing phases on performance, diet digestibility, weight of digestive organs, carcass traits, and economic evaluation. A total of 40 barrows with 44.59 ± 5.16 kg initial weight were fed diets with 0%, 7%, 14%, and 21% detoxified castor bean cake. Increasing levels of detoxified castor bean cake in diets resulted in linear worsening in the average daily g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, in a similar study conducted in the city of Varamin (Tehran, Iran), the energy efficiency was calculated to be 144.66 counting the produced biomass, and 3.81 for the produced seeds only [28]. In the research carried out in Brazil, the energy productivity was reported to be 117 0.02 and 0.14 kg.MJ -1 in traditional and mechanized farming systems respectively [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a similar study conducted in the city of Varamin (Tehran, Iran), the energy efficiency was calculated to be 144.66 counting the produced biomass, and 3.81 for the produced seeds only [28]. In the research carried out in Brazil, the energy productivity was reported to be 117 0.02 and 0.14 kg.MJ -1 in traditional and mechanized farming systems respectively [17].…”
Section: Resultsmentioning
confidence: 99%
“…After the oil processes, the biomasic waste is used in different recovery processes to obtain energy, biodiesel, animal food, compost, paper, water retenders, etc. [16][17][18]. The seeds of Ricinus communis, which contain ricin, a water-soluble toxin, have limited uses for humans and animals [19].…”
Section: Introductionmentioning
confidence: 99%